2021
DOI: 10.21037/tlcr-20-721
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II trial of uracil/tegafur and cisplatin versus pemetrexed and cisplatin with concurrent thoracic radiotherapy for locally advanced unresectable stage III non-squamous non-small cell lung cancer: NJLCG1001

Abstract: Background: The optimal regimen for concurrent chemoradiotherapy (CCRT) of locally advanced nonsquamous non-small cell lung cancer (NSCLC) was not definitive. We conducted randomized phase II study, NJLCG0601, and chemoradiotherapy with uracil/tegafur (UFT) and cisplatin achieved promising efficacy without severe toxicities. Here, we evaluated between this regimen and pemetrexed plus cisplatin in chemoradiotherapy for stage III non-squamous NSCLC.Methods: Patients with inoperable stage III non-squamous NSCLC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…All clinical trial groups have abundant experience and strong achievements, The JCOG Lung Cancer Study Group reported results of four phase 3 trials between 2014 and 2016, 15 , 16 , 17 , 18 and the WJOG also reported results of four phase 3 trials targeting lung cancer in the past 5 years. 19 , 20 , 21 , 22 The NJLCG and TORG have reported four 23 , 24 , 25 , 26 and three 12 , 27 , 28 randomized phase 2 trials, respectively, and several other single-arm trials in the past 5 years. The National Cancer Center Hospital EAST was the lead site of the SPECTRA trial, and the primary investigator, Niho Seiji, has abundant experience from many clinical trials, 29 , 30 , 31 , 32 , 33 which made it possible to constitute a reliable data set.…”
Section: Discussionmentioning
confidence: 99%
“…All clinical trial groups have abundant experience and strong achievements, The JCOG Lung Cancer Study Group reported results of four phase 3 trials between 2014 and 2016, 15 , 16 , 17 , 18 and the WJOG also reported results of four phase 3 trials targeting lung cancer in the past 5 years. 19 , 20 , 21 , 22 The NJLCG and TORG have reported four 23 , 24 , 25 , 26 and three 12 , 27 , 28 randomized phase 2 trials, respectively, and several other single-arm trials in the past 5 years. The National Cancer Center Hospital EAST was the lead site of the SPECTRA trial, and the primary investigator, Niho Seiji, has abundant experience from many clinical trials, 29 , 30 , 31 , 32 , 33 which made it possible to constitute a reliable data set.…”
Section: Discussionmentioning
confidence: 99%
“…1 . Among the 248 studies, 174 studies (85 Asian and 89 non-Asian) with 20,999 patients examined definitive CRT without immunotherapy, 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Resultsmentioning
confidence: 99%